2015
DOI: 10.5301/ejo.5000675
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Thickness in Systemic Arterial Hypertension

Abstract: The results of this study demonstrated that choroidal thickness decreases in patients with systemic arterial hypertension. This may be caused by arteriolar sclerosis and vascular contraction caused by high intravascular pressure in the choroid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
90
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(98 citation statements)
references
References 22 publications
(26 reference statements)
3
90
1
2
Order By: Relevance
“…[252627] The present study revealed reduced SFCT in CADASIL patients. Young adults with systemic arterial hypertension were shown to have significantly lower SFCT as compared to that in healthy controls.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…[252627] The present study revealed reduced SFCT in CADASIL patients. Young adults with systemic arterial hypertension were shown to have significantly lower SFCT as compared to that in healthy controls.…”
Section: Discussionmentioning
confidence: 49%
“…Young adults with systemic arterial hypertension were shown to have significantly lower SFCT as compared to that in healthy controls. [25] Thinner SFCT is also seen in diabetic patients without diabetic retinopathy,[2627] and in patients with migraine. [28] In addition, a decrease in mean SFCT was also described in ocular ischemic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that the patients in the two treatment groups had comparable baseline characteristics, this limitation might have influenced the results of this study. Previous studies have shown that the choroidal thickness is associated with various factors, including diurnal variation,26 refractive error or axial length,27 and the presence of hypertension,28 and diabetes mellitus 29. Additionally, the intake of water30 or coffee31 can also influence the choroidal thickness.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] In addition, it is known that ChT is affected by various factors such as blood pressure, age, gender, time of the day, refractive status, axial length, and forced hyperopic or myopic defocus. 2,[9][10][11] Further, a recent experimental study showed that anti-muscarinic agents could affect ChT. 12 Therefore, in the present study, we aimed to investigate the effects of tropicamide and cyclopentolate, which are two anti-muscarinic agents commonly used in the ophthalmologic practice, on subfoveal ChT measured by EDI OCT in healthy adults.…”
Section: Introductionmentioning
confidence: 99%